Copyrights and Creativity: Evidence from Italian Opera in the Napoleonic Age - Giorcelli, Michela; Moser, Petra (Journal of Political Economy, 2020)
This paper exploits variation in the adoption of copyrights within Italy—due to the timing of Napoléon’s military victories—to investigate the causal effects of copyrights on creativity. Baseline regressions compare changes in opera production across Italian states with and without copyrights. This analysis yields three main results. First, the adoption of copyrights led to a significant increase in the number of newly created operas. Second, copyrights raised the quality of new operas, measured both by their immediate success and by their longevity. Third, there were no benefits from copyright extensions beyond the life of the original creator.